A crença sobre a morte e o coping religioso-espiritual em pacientes internados com doenças crônicas - Silva, Virginia Maria Terra (2016)
The human being is understood as an integral being, complex, which has multiple dimensions: social, biological, psychological, anthropological, spiritual and others. As its biological dimension, the man presents the possibility of physical illness, which means that the body requires care. The sick away from humans in health and safety conditions, approaching them directly from the finitude and vulnerability condition, leading us to contact the major uncertainties of life: suffering of disease and death. Religiosity and spirituality are important coping strategy for human when faced with borderline situations. When people turn to religion to cope with stress is the religious and spiritual coping. The objective of this research was to evaluate the relationship between the views on death and the religious-spiritual coping in patients with chronic diseases hospitalized. The study included ten patients hospitalized for chronic disease complications Medical Clinic Unit of a public hospital in the city of Uberlândia/MG. two psychological scales were used: Scale Religious-Spiritual Coping Brief (CRE-Brief Scale) and Scale Brief Diverse Perspectives of Death and a structured interview (audiogravada) on the subject of death and religious and spiritual coping. The results indicated that 80% of the sample (N = 8) consisted of patients hospitalized due to chronic diseases, while 20% accounted for patients with AIDS complications. Analyzing the results of scale CRE-Brief, it emphasizes the use of strategies of religious and spiritual coping by participants as compared to CRE Total, all study participants had average or high scores for this index, with a low utilization CRE negative and average utilization CRE Positive. Regarding views on death, the results obtained by the Different Perspectives Quick Scale on Death suggest that this sample agrees with the view death as something that is part of the natural cycle of life (M8 - Death as a natural end) and features the prospect of death as uncertainty, mystery and ignorance (M4 - death as Unknown). The correlations between the measures the factors and items of CRE-Bref and dimensions of Short scales on different perspectives of Death notes the prevalence of correlations of M4 dimensions - Death as unknown and M8 - Death as a natural order to the creditor scale soon. In the interview analysis revealed a positive influence of religion/ spirituality on health, from the perspective of the respondent, highlighting the protection promoted by religion. It also noticed the use of prayer as a coping strategy of hospitalization and illness. Regarding the interview about the topic of death, there was a predominance of issues related to "afterlife", "unknown" and "abandonment", which are associated with the visions of death and mystery and death as a natural end. In the interviews there belief clues about death as a terrifying mystery connected, so the unknown and the feeling of fear on the same. The experience of illness can therefore be considered as a source of vulnerability, since it is present personal perception of danger (external) - own illness and possible death, especially in those patients undergoing ICU - and where control is insufficient for the sense of security, since the hospital providing care to the patient are delegated to third parties and patients assume a passive role. This fact is important and relevant to health professionals who deal daily with patients hospitalized for chronic diseases, since the recourse to religion and spirituality as a coping strategy that psychic movement was not constituted in a form of negative distance or even denial of health condition. On the contrary, it refers to a movement in search of comfort and security provided by the religion and spirituality.